Long‐term (64 years) annual burning lessened soil organic carbon and nitrogen content in a humid subtropical grassland. (11th October 2021) - Abdalla, Khatab; Chivenge, Pauline; Ciais, Philippe; Chaplot, Vincent
ABSTRACT: Burning has commonly been used to increase forage production and nutrients cycling in grasslands. However, its long‐term effects on soil organic carbon (SOC) and nitrogen (N) pools within the aggregates and the relation between aggregates‐associated SOC and soil CO2 emissions need further appraisal. This study evaluated the effects of 64 years of annual burning on SOC and N dynamics compared to annual mowing and undisturbed treatments in a grassland experiment established in 1950. Soils were sampled from four depths representing the upper 30 cm layer and fractionated into macroaggregates, microaggregates and silt + clay fractions. The macroaggregates were further fractionated into three occluded fractions. The SOC in the bulk soil and aggregates were correlated to soil CO2 effluxes measured under field conditions. Compared to the undisturbed treatment, annual burning decreased aggregates stability, SOC and N in the upper 30 cm layer by 8%, 5% and 12%, respectively. Grassland mowing induced greater aggregates stability than burning only in the upper 5 cm. Burning also decreased SOC in the large macroaggregates (e.g., 0–5 cm) compared to mowing and the undisturbed grasslands but proportionally increased the microaggregates and their associated SOC. Soil N associated with aggregates decreased largely following grassland burning, for example, by 8.8‐fold in the microaggregates within the large macroaggregates at 20–30 cm compared to the undisturbed grassland. Burning also increased soil CO2 emissions by 33 and 16% compared to undisturbed and mowing, respectively. The combustion of fresh C and soil organic matter by fire is likely responsible for the low soil aggregation, high SOC and N losses under burned grassland. These results suggested a direct link between grass burning and SOC losses, a key component for escalating climate change severity. Therefore, less frequent burning or a rotation of burning and mowing should be investigated for sustainable grasslands management. Abstract : A 64‐years of annual burning caused significant loss of soil organic carbon and nitrogen content compared to annual mowing and undisturbed grasslands. These results were mainly explained by the adverse effect of fire on soil aggregates stability. In addition to soil carbon and nitrogen losses, fire also produces more greenhouse gases, i.e., COx, Nx O and CH4, during biomass burning suggesting a significant impact on global warming. Hence, grassland burning could increase grass quality and prevent bush encroachments; integrating other management such as mowing, rest, or controlled grazing with burning could be investigated for grassland and environmental conservations.